Analiza temperatur in toplotne energije pri odrezavanju - Milfelner, Matjaž (Strojniški vestnik, 2001)
This paper describes an analysis of the temperatures and energies which occur during the cutting process. The influence of the temperature on the cutting face and the cutting insert edge is very important since it causes wear of the tool face and of the tool cutting edge and thus the tool's resistance to wear is reduced. The final part of the paper shows an example of a simulation of the isothermal lines on the tool cutting edge for the case of a change of cutting speed and a change of the tool geometry.
Keywords: energije toplotne; temperature; ploskve strižne; ploskve cepilne; odrezavanje; temperaturno polje; toplotne razmere